Evaluation of macro and meiobenthic community structure and distribution in the hybrid ocean thermal energy conversion discharge area of Port Dickson - Leng, Qingxue; Mohamat-Yusuff, Ferdaus; Mohamed, Khairul Nizam; Zainordin, Nazatul Syadia; Hassan, Zafri (Nature Research, 2025)
Over the past two decades, the technology underlying Hybrid Ocean Thermal Energy Conversion (H-OTEC) power plants have progressively matured. These advancements position H-OTEC as a promising alternative energy source with significant potential to replace traditional power plants. The cold discharge from H-OTEC Pilot Plants reduces the temperature of receiving water bodies, thereby directly or indirectly impacting the marine ecological environment. A one-year study was conducted around a pilot-stage 1.0 MW H-OTEC Pilot Plant in Port Dickson to investigate the effects of cold discharge on macro- and meiobenthic communities across different seasons. Apart from the water temperature within a 5-meter range affected by the H-OTEC cold discharge, the impact on other water quality indicators is negligible. A total of 22 macrobenthic species belonging to 4 phyla and meiobenthic organisms belonging to 9 taxa were identified across 15 sampling points. This study demonstrated that cold emissions had a limited impact on the abundance and community structure of benthic organisms across different seasons. The abundance of benthic organisms exhibited a significant increase in Inter-monsoon, followed by a significant decrease in Dry season. Moreover, there was a positive correlation observed between the abundance of benthic organisms and the content of water temperature, conductivity, gavel, sediment pigments and total organic matter. This study identified significant seasonal variations in the structure of both macro- and meio-benthic communities. Specifically, Umbonium vestiarium and other gastropoda were the dominant taxa and primary contributors to the observed significant changes in the structure of macro- and meio-benthic communities, respectively. Nevertheless, further study with a higher discharge volume of the outfall is crucial to assist in the outfall pipe placement of the mega-scale OTEC electricity plant. This study provided crucial insights into the ecological impacts of cold emissions from H-OTEC Pilot Plants in tropical coastal areas.